Attitudes and perceptions for Covid-19 of migrants & refugees living in a camp: Quantitative Study. - Provias, Georgios; Karampasis, Christos; Argyrou, Ourania; Theofanidis, Dimitrios (Health & Research Journal, 2025)
Background: The outbreak of the coronavirus (COVID-19) pandemic profoundly altered daily life worldwide. Both the virus itself and the preventive measures implemented to limit its transmission generated heightened levels of stress and fear. Refugees and migrants, owing to their inherent vulnerabilities, encountered additional challenges in coping with these circumstances. Method and Material: The purpose of this paper is to investigate the attitudes and perceptions of the refugee population residing in shelter facilities in Northern Greece, regarding the Covid-19 infection and the impact of the infection on their mental health status and daily behavior patterns. The “Psychological and Behavioral Response to the Coronavirus (Covid-19) Pandemic” questionnaire was administrated to a random sample of 66 men and 54 women who were living in the Refugee-Migrant Center, in the suburbs of Thessaloniki during the period of March-April 2021. Results: Most respondents reported adherence to hygiene measures (88%–100%). Non-asylum holders exhibited a greater psychological impact (73%), primarily due to anxiety and fear (90%). Compliance with hygiene measures was reported by 81% of those who had previously been ill, compared to 96% among those who had not contracted the disease. Conclusions: This study identified significant effects at both psychological and behavioral levels. Heightened anxiety and fear influenced participants across the sample, leading many to avoid routine daily activities. The majority demonstrated adherence to government-mandated preventive measures. However, individuals who perceived the situation as less severe than portrayed exhibited lower levels of psychological impact compared to those with more pessimistic views.